2021
DOI: 10.1186/s12879-021-06754-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine-needle aspiration to improve diagnosis of melioidosis of the head and neck in children: a study from Sarawak, Malaysia

Abstract: Background Melioidosis, the infection caused by Burkholderia pseudomallei, is associated with a high case fatality rate, due in part to difficulties in clinical recognition and diagnostic confirmation of the disease. Although head and neck involvement is common in children, specific disease manifestations differ between geographic regions. The aim of this study was to provide a detailed description of melioidosis of the head and neck among children in Sarawak, Malaysia, and determine if fine-ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In Thailand and Cambodia, 65% and 33% of children with melioidosis, respectively, present with head and neck manifestations, with the salivary glands predominantly involved [12,13]. In a previous report, we showed that nearly 60% of children with melioidosis in Sarawak, Malaysia, have head or neck manifestations [14]. Unlike children in Thailand and Cambodia, however, we found that cervical lymph nodes were the dominant organ site involved.…”
Section: Discussionmentioning
confidence: 48%
“…In Thailand and Cambodia, 65% and 33% of children with melioidosis, respectively, present with head and neck manifestations, with the salivary glands predominantly involved [12,13]. In a previous report, we showed that nearly 60% of children with melioidosis in Sarawak, Malaysia, have head or neck manifestations [14]. Unlike children in Thailand and Cambodia, however, we found that cervical lymph nodes were the dominant organ site involved.…”
Section: Discussionmentioning
confidence: 48%
“…The microbiological specimen collection and processing procedures have been described elsewhere. 9 Clinical definitions used are shown in Table 1. Statistical analysis was performed using SPSS Statistics 21.…”
mentioning
confidence: 99%